Building a Space Shooter Game: Utilizing Scratch for an Engaging Action Game - Juanda, Juanda; Zikrillah, Zikrillah; Nasrullah, Nasrullah (Gameology and Multimedia Expert, 2024)
The rapid advancement of computer technology in the field of animation is marked by the emergence of various programming applications that simplify the creation of animations, one of which is Scratch. Games have become a popular form of entertainment across various audiences, including the Space Shooter game, which is designed to provide an exciting and entertaining action experience. In this game, players are challenged to control a spaceship and fight enemies that appear from the top of the screen, while avoiding enemy attacks and shooting them to earn points. The objective of the Space Shooter game development is to create a game that combines attractive graphics, addictive gameplay mechanics, and increasing difficulty levels as the player progresses. Additionally, the game aims to test the player's endurance in surviving as long as possible while collecting the highest score. The development of this game is expected to offer a fun and challenging gaming experience, while also improving players' decision-making skills and reflexes during gameplay.